Factors associated with depressive symptoms in people living with HIV attending antiretroviral clinic at Fitche Zonal Hospital, Central Ethiopia: cross-sectional study conducted in 2012 - Yeneabat T (Dove Medical Press, 2017)
Tebikew Yeneabat,1 Asres Bedaso,2 Tadele Amare3 1Department of Midwifery, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 2School of Nursing and Midwifery, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 3Department of Psychiatry, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia Background: Depression is one of the most common psychiatric disorders with the prevalence rate ranging from 5% to 10% in the general population and about 60% in people living with human immunodeficiency virus (PLHIV). It has been reported to be more common among women living with HIV. In HIV patients, depression can have negative impacts on their quality of life.Objective: This study was aimed at identifying the prevalence of depressive symptoms and associated factors among PLHIV attending the antiretroviral therapy clinic at Fitche Zonal Hospital.Methods: It was a cross-sectional study conducted among PLHIV in Fitche Zonal Hospital from February 15 to March 15, 2012. Center for Epidemiologic Studies Depression tool was used to collect data from 390 respondents. Both the bivariate and multivariable logistic regression analyses were carried out and variables with P<0.25 in the bivariate logistic regression analysis were entered into multivariable logistic regression analysis and statistical significance was declared at P<0.05.Results: Of the total 390 respondents included in the analysis, the prevalence of depressive symptoms was 76.7%, ranging from mild to moderate (33.6%) to major (43.1%), and the highest proportion was observed among individuals with food insecurity accounting for 287 (79.3%). Food insecurity (adjusted odds ratio [AOR] =3.832 [1.575–9.322]), non-ownership of livestock (AOR =2.17 [1.157–4.104]), and opportunistic infections (AOR =5.20 [1.342–20.156]) were significantly associated with depressive symptoms.Conclusion and recommendations: Depressive symptoms were prevalent in PLHIV. Social disparities were important factors of depressive symptoms. Integration of mental health care services with HIV/acquired immune deficiency syndrome-related health care services at all health care levels was necessary. It was recommended that government and non-government organizations should provide assistance to the PLHIV to encourage their involvement in income-generating activities. Keywords: depression, PLHIV, Fitche, CES-D